2019
DOI: 10.1093/plankt/fbz010
|View full text |Cite
|
Sign up to set email alerts
|

Individual body size as a predictor of lipid storage in Baltic Sea zooplankton

Abstract: The size structure of a zooplankton community is frequently used as a trait reflecting functional properties, including biochemical composition. Therefore, a shift in zooplankton body size can reflect shifts in the nutritional quality of zooplankton. In dominant Baltic copepods and cladocerans, neutral to polar lipid ratio (NL/PL ratio), a proxy for the mass-normalized lipid storage, was determined and related to individual body weight. A significant relationship between the NL/PL ratio and body weight was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The result would be more carbon cycling in the pelagic, favoring the accumulation of small copepods. Smallerbodied zooplankton are lower in energy density and are often lipid-poor relative to larger zooplankton (Siddon et al 2013, Gorokhova 2019. The increase in smaller-sized zooplankton taxa may also accompany a decline in the lipid-rich Calanus spp., though it has been suggested that the increasing number of smaller zooplankton (with some lipid storage) may compensate for the loss of lipid-rich species of Calanus (Renaud et al 2018).…”
Section: )mentioning
confidence: 99%
“…The result would be more carbon cycling in the pelagic, favoring the accumulation of small copepods. Smallerbodied zooplankton are lower in energy density and are often lipid-poor relative to larger zooplankton (Siddon et al 2013, Gorokhova 2019. The increase in smaller-sized zooplankton taxa may also accompany a decline in the lipid-rich Calanus spp., though it has been suggested that the increasing number of smaller zooplankton (with some lipid storage) may compensate for the loss of lipid-rich species of Calanus (Renaud et al 2018).…”
Section: )mentioning
confidence: 99%
“…The present study revealed that copepods distributed and fed on to the sardine in the offshore area were larger (heavier) than those in the coastal area. In general, larger copepods tend to accumulate more lipids because of larger body cavities (Gorokhova, 2019; Kattner & Hagen, 2009; Lee et al, 2006). Hence, the lipid content of zooplankton assemblages might vary in association with the copepod abundance and the individual copepod mass.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature has direct effects on metabolic rates of aquatic organisms and fatty acid modifications in their membrane lipids to maintain fluidity and function (Parrish, 2013). Moreover, warming is shifting the plankton communities towards smaller size and thus, reduced individual lipid content (Daufresne et al, 2009;Mäkinen et al, 2017b;Renaud et al, 2018;Gorokhova, 2019), and towards increased heterotrophy, which decreases the availability of DHA and EPA (Dahlgren et al, 2011). The Baltic Sea is a large pool of brackish water, where salinity determines the species distribution and community structure (Diekmann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%